Cookbooks for children in the USA in the second half of the 19th and 20th centuries – tendencies and development trends - Has-Tokarz, Anita Lidia (Folia Toruniensia, 2020)
Thesis / Purpose: The aim of the article is to investigate the origins and development of cookbooks intentionally addressed to children published in the USA in the second half of the 19th and 20th centuries. The aim was to indicate specific types of these publications and to identify social and economic factors influencing their evolution. Research method:The source material for the analysis was obtained from the digital resources of cookbook collections in the public domain, such as Ann Hertzler Children's Cookbook & Nutrition Literature Collection, Johnson & Wales University Culinary Arts Museum and others. In total, several dozen copies issued in the USA in the years 1876-1998 and other artifacts belonging to the area of children's culinary culture in this geographical area were analyzed. Results / Conclusions:The history of cookbooks for children in the USA begins in 1876 and continues to this day. The genesis of the phenomenon is associated with the dissemination of Enlightenment ideas, especially the new model of upbringing and the psychosocial emancipation of the child along with the socio-economic changes, the expansion of the circle of readers, the emergence of a new group of buyers - middle-class children. Early American cookbooks for children took the form of literary culinary stories, the so-called cookstory or culinary story. They were used to teach girls to cook, they were a tool of socialization to act as a housewife. Since the beginning of the 20thcentury, we have been observing a dynamic development of new trends in these publications, such as verse cookbooks and brochures advertising well-known food brands, the so-called culinary emphemera. Cookbooks for boys appeared on the market in the mid-20thcentury. In the 1970s, there appeared guides aimed at adolescents promoting healthy lifestyle and diets (vegan and vegetarian), books related to the heroes of childhood readings and popular media icons for children. Nowadays, attention is drawn to the variety of formats and high editorial attractiveness of these publications and their strong relationship with the toy and media industry.